Investigating the regulatory role of HvANT2 in anthocyanin biosynthesis through protein–motif interaction in Qingke - Wang, Yan; Chen, Lin; Yao, Youhua; Chen, Lupeng; Cui, Yongmei; An, Likun; Li, Xin; Bai, Yixiong; Yao, Xiaohua; Wu, Kunlun (PeerJ, 2024)
Background Currently, there are no reports on the HvbHLH gene family in the recent barley genome (Morex_V3). Furthermore, the structural genes related to anthocyanin synthesis that interact with HvANT2 have yet to be fully identified. Methods In this study, a bioinformatics approach was used to systematically analyze the HvbHLH gene family. The expression of this gene family was analyzed through RNA sequencing (RNA-seq), and the gene with the most significant expression level, HvANT2, was analyzed using quantitative reverse transcription polymerase chain reaction (qRT-PCR) in different tissues of two differently colored varieties. Finally, structural genes related to anthocyanin synthesis and their interactions with HvANT2 were verified using a yeast one-hybrid (Y1H) assay. Results The study identified 161 bHLH genes, designated as HvbHLH1 to HvbHLH161, from the most recent barley genome available. Evolutionary tree analysis categorized barley bHLH TFs into 21 subfamilies, demonstrating a pronounced similarity to rice and maize. Through RNA-Seq analysis of purple and white grain Qingke, we discovered a significant transcription factor (TF), HvANT2 (HvbHLH78), associated with anthocyanin biosynthesis. Subsequently, HvANT2 protein-motifs interaction assays revealed 41 interacting motifs, three of which were validated through Y1H experiments. These validated motifs were found in the promoter regions of key structural genes (CHI, F3’H, and GT) integral to the anthocyanin synthesis pathway. These findings provide substantial evidence for the pivotal role of HvANT2 TF in anthocyanin biosynthesis.
Keywords: Qingke; Anthocyanin; HvANT2; HvbHLH gene family; Y1H